Toward a theory of development involvement: understanding readiness to develop - Walter, Matthew Ryan, author; Thornton, George C., III, advisor; Feller, Richard W., committee member; Hautaluoma, Jacob E., committee member; Rosén, Lee A., committee member (Colorado State University. Libraries, 2005)
This study presents an integrative theoretical framework for understanding the relationship between some individual difference variables and developmental involvement behaviors. It posits that a learning and development orientation, measured by a construct called readiness to develop, mediates the relationship between specific individual-difference variables and development participation. The nomological network of readiness to develop is presented and some of the proposed associations are empirically investigated. A developmental assessment center program was designed and utilized to gather data over a two-year period. Consistent with previous research, the results illustrate that openness to experience and extraversion significantly influence an individual' s level of readiness to develop. The findings also show that readiness to develop predicts development activity, as measured through a follow-up evaluation, four months post-assessment. The criteria for testing the general hypothesis, that readiness to develop mediates the relationship between the individual-difference variables and development participation, were not met. Both the theoretical and practical implications of the findings are discussed.